School food and nutrition policy, monitoring and evaluation in the USA - Hirschman, Jay; Chriqui, Jamie F (Public health nutrition, 2013)
To provide an overview of school food and nutrition monitoring from 1980 to the Healthy Hunger-Free Kids Act of 2010 and data on school food availability in the USA. A review of the history of school food and nutrition policy, monitoring and evaluation efforts in the USA over the past three decades. USA. School food service, school districts and schools nationwide. The school food environment in the USA is governed by a patchwork of federal, state and local laws and policies. The federal government has primary authority over the school meal programmes and has recently issued updated regulations governing the food and nutrient requirements for meals sold or served through the National School Lunch and School Breakfast Programs. Competitive foods (i.e. foods and beverages sold/served outside the meal programmes) are governed primarily by state and district laws and policies, although new federal regulations are expected to set minimum standards in this area. The USA has a long history of data monitoring and evaluation funded by government and private foundations which has enabled decision makers to monitor progress and opportunities to improve the foods and beverages made available to students in school. School food-related monitoring and evaluation research has been highly influential in influencing legislation and policy, leading to improvements in the foods and beverages available to children at school as part of planned meals and individual items sold outside the meal programmes. The lessons learned from the US experience provide insights that may be valuable for implementation, monitoring and evaluation of school food programmes in other countries.